New hypoglycaemic therapy in frail older people with diabetes mellitus-phenotypic status likely to be more important than functional status. (November 2020) - Abdelhafiz, A.H.; Emmerton, D.; Sinclair, A.J.
Abstract: Frail older people are largely excluded from clinical trials and therefore glycaemic targets and optimum hypoglycaemic therapy in this group has not been fully investigated. Guidelines generally recommend tight glycaemic control in functionally fit individuals and relaxed targets in frail ones mainly due to the fear of hypoglycaemia. The newly introduced sodium glucose cotransporter-2 inhibitors and the glucagon like peptide-1 receptor agonists have shown benefit that is independent of glycaemic control and a minimal risk of hypoglycaemia. However, guidelines still express caution about its use in frail older people due to fear of other side effects such as weight loss, hypotension and falls. Some frail older people will miss out on the benefits of this new therapy if frailty is considered as a one entity with a blanket application of guidelines. We propose that frailty should be viewed as two distinct metabolically different phenotypes, the sarcopenic-obese, in which new therapy will improve their metabolic profile and should be liberally used if no contraindications, and the anorexic-malnourished phenotype in which the new therapy should be cautiously considered. In other words, glycaemic targets should be driven by individual's overall function but the use of new therapy should be driven by frailty phenotype.